Worker Characteristics and Measures Associated With Patient and Visitor Violence in the COVID-19 Pandemic: A Multilevel Regression Analysis From China - Guo, Ya-qian; Huang, Ju; Xu, Na-na; Ma, Xiao-jing (Frontiers in Public Health, 2022)
Objective To analyze the patient and visitor workplace violence (PVV) toward health workers (HWs) and identify correlations between worker characteristics, measures against violence and exposure to PVV in COVID-19 pandemic. Methods A cross-sectional survey utilizing the international questionnaires in six public tertiary hospitals from Beijing in 2020 was conducted, and valid data from 754 respondents were collected. Multilevel logistic regression models were used to determine the association between independents and exposure to PVV. Results During COVID-19 pandemic and regular epidemic prevention and control, doctors were 5.3 times (95% CI = 1.59 17.90) more likely to suffer from physical PVV than nurses. HWs most frequently work with infants were 7.2 times (95% CI = 2.24 23.19) more likely to suffer from psychological PVV. More than four-fifth of HWs reported that their workplace had implemented security measures in 2020, and the cross-level interactions between the security measures and profession variable indicates that doctors in the workplace without security measures were 11.3 times (95% CI = 1.09 116.39) more likely to suffer from physical PVV compared to nurses in the workplace with security measures. Conclusion Doctors have higher risk of physical PVV in COVID-19 containment, and the security measures are very important and effective to fight against the physical PVV. Comprehensive measures should be implemented to mitigate hazards and protect the health, safety, and well-being of health workers.